Origin of Phonon Glass–Electron Crystal Behavior in Thermoelectric Layered Cobaltate. (13th June 2013) - Wu, Lijun; Meng, Qingping; Jooss, Christian; Zheng, Jin‐Cheng; Inada, H.; Su, Dong; Li, Qiang; Zhu, Yimei
Abstract Measurement of local disorder and lattice vibrations is of great importance for understanding the mechanisms whereby thermoelectric materials efficiently convert heat to electricity. Attaining high thermoelectric power requires minimizing thermal conductivity while keeping electric conductivity high. This situation is achievable by enhancing phonon scattering through specific structural disorder (phonon glass) that also retains sufficient electron mobility (electron crystal). It is demonstrated that the quantitative acquisition of multiple annular‐dark‐field images via scanning transmission electron microscopy at different scattering‐angles simultaneously allows not only the separation but also the accurate determination of static and thermal atomic displacements in crystals. Applying the unique method to the layered thermoelectric material (Ca2CoO3)0.62CoO2 discloses the presence of large incommensurate displacive modulation and enhanced local vibration of atoms, largely confined within its Ca2CoO3 sublayers. Relating the refined disorder to ab initio calculations of scattering rates is a tremendeous challenge. Based on an approximate calculation of scattering rates, it is suggested that this well‐defined deterministic disorder engenders static displacement‐induced scattering and vibrational‐induced resonance scattering of phonons as the origin of the phonon glass. Concurrently, the crystalline CoO2 sublayers provide pathways for highly conducting electrons and large thermal voltages.